Teoremat Coase'a jako przykład systemu ekwifinalnego - Jakubczyk, Zbigniew (Coase Theorem as an Example of an Equifinal System, 2009)
The article presents the phenomenon of equifinality based on the example of Coase theorem. By equifinality we understand a situation in which it is possible to reach the same final state originating from different initial conditions and using different ways. At the beginning of the paper traditional and contemporary approach to equifinality phenomenon, both in social and natural sciences, is discussed. In the next part the main ideas of Coase's theorem are presented. In the last part of the article some elements of equifinality of Coase's theorem are discussed.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 53-59